A review of neonatal peripherally inserted central venous catheters in extremely or very low birthweight infants based on a 3-year clinical practice: Complication incidences and risk factors - Wu, Yaohua; Yan, Jing; Tang, Mengyan; Hu, Yanling; Wan, Xingli; Li, Xiaowen; Chen, Qiong; Li, Xia (Frontiers in Pediatrics, 2022)
Background The application of peripherally inserted central venous catheters (PICCs) in neonates has proven effective in avoiding repetitive insertions and excessive use of transfusion consumables. However, the frequent occurrence of PICC-associated complications deserves special attention, especially in extremely or very low birthweight (E/VLBW) infants, which in turn affects the quality of neonatal PICC practice. Therefore, we conducted a retrospective study of a 3-year clinical practice of neonatal PICCs in E/VLBW infants to understand the incidences of various catheter-related complications and their risk factors to help form an empirical summary and evidence-based guidance for the improvement of practice. Methods A retrospective study was conducted based on a 3-year practice of neonatal PICCs in E/VLBW infants. Neonatal health records were collected, including demographic characteristics, PICC placement data, and treatment information. Results A total of 519 E/VLBW infants were included in this study. There were 77 cases of complications involving 72 infants with an overall incidence of 12.13%. The order of incidences of different complications from high to low was phlebitis (7.71%), malposition (3.66%), leakage (1.35%), pleural effusion (1.15%), central line-associated bloodstream infection (0.58%, 0.25/1,000d), and accidental removal (0.38%). Multivariate analysis revealed that the inserted vessel was an independent risk factor for PICC-associated complications (mainly phlebitis; p = 0.002). Neonatal PICCs inserted in the axillary vein were only one-tenth (p = 0.026) as likely to cause phlebitis as in the basilic vein, whereas when applied in the saphenous vein, neonatal PICCs were five times as likely to cause phlebitis (p = 0.000). Conclusion E/VLBW infants might be more inclined to develop PICC-associated phlebitis. Catheters inserted in the axillary or basilic vein are preferred if possible.